Deckard - a tree-based, scalable, and accurate code clone detection tool (version 1.2.1) - JIANG, Lingxiao (Institutional Knowledge at Singapore Management University, 2011)
Deckard is a tree-based, scalable, and accurate code clone detection tool. It is also capable of reporting clone-related bugs. For more information, pls refer to readme.txt. The latest version is available from Deckard repository on Github. https://github.com/skyhover/Deckard